Face recognition and identification system (FaceRec) / Khew Jye Huei - Khew , Jye Huei (2004)
Face recognition is a technique to identify an individual by his/her physical characteristic and has been of interest to a growing number of researchers due to its applications on security. Several different algorithms have been proposed for computer recognition of human faces. It describes the implementation and functions of a working system that performs the recognition and identification of human faces using the implement algorithms. Java is use as programming language to develop the Face Rec system and Microsoft Access as the database to store and access the fa e images for the training set. Besides that, the system will build in Windows 2000 Professional Operating System. The project approaches the research and development process as a two dimensional recognition problem, capturing the face image by using the web camera. The process begins by preparing the database of face images for the training set before proceeding to the recognition technique for identification using eigenfaces approach. Various experiments are carried out to evaluate the performance of the working system to determine its performance and results. With FaceRec this system can perform recognition and identification of human faces for security purposed under certain constraint conditions in a fast and flexible way. So that, the access control will be more secure. It also allow for further research and development on the same or new approach.